Upaya Meningkatkan Hasil Belajar dengan Metode Kontekstual - Sofyan Sofyan; Ferdiaz Saudagar; Bradley Setiyadi (Universitas Indraprasta PGRI Jakarta, 2020)
The strategy for generating student activity in the learning process is to use appropriate methods or models that learning can make students as subjects who try to explore themselves, solve their own problems of a concept being studied, while the teacher acts more as a motivator and facilitator. For this reason, this class action research was conducted to see whether contextual methods could increase student motivation in learning materials for Class XI of Administration Procedures of Office Administration 3 Department of Office Administration at SMKN 1 Kota Jambi. The subjects in this study were students of class XI of Office Administration 3 Department of Office Administration at SMKN 1 Kota Jambi, totaling 40 students, with 28 women and 12 men. This class action research was carried out in two cycles, each cycle was a process flow which includes four stages, namely: (1) Planning, (2) Implementation, (3) Observation, (4) Reflection. From reflection on cycle I, if it appeared that students had not reached the minimum value, then cycle II was performed to perfect cycle I. The Improvement of student learning outcomes seemed to be seen from Pre-Cycle to Cycle I and looked even more apparent from Cycle I to Cycle II.